Uma missiva contra o peronismo tupiniquim - Carlos Lacerda, Tribuna da Imprensa e a carta Brandi (1955) - Santos, Rodolpho Gauthier Cardoso dos (2017)
This article analyses an episode of the Political History of Brazil known as Brandi letter, which controversy occurred some days before the 1955’s Brazilian election for president. The main historical source of this paper is the carioca newspaper Tribuna da Imprensa, whose ownership was in the hands of Carlos Lacerda, federal deputy from UDN (União Democrática Nacional). In September of that year, this newspaper scandalously published a letter attributed to an argentinian peronist deputy named Antonio Brandi. The message would have been sent to João Goulart that was by that time the president of the PTB (Partido Trabalhista Brasileiro) and a candidate for the vice-presidency with the support of Juscelino Kubitschek. The controversial content of the letter, which explicitly tells about the formation of “brigades of shock workers” and the acquisition of products from Cordoba’s military factory, disrupted the electoral process. Politicians and conservative newspaper alleged that the election of the trabalhista leader would carry the country to a dictatorship with the Argentinian support. This academic work analyses the agency of Tribuna da Imprensa and of his owner in this convulsed moment of Brazilian politics, in which the antiperonist imaginary was very Strong.